Numerical study of semi‐rigid behaviour joints for slender purlins. Issue 3 (16th September 2019) - Gutiérrez, Ruth María; Loureiro, Alfonso; Reinosa, Jose Manuel; Lopez, Manuel
ABSTRACT: Connections made in the multi‐span purlins are usually analysed employing the 3 points load test. In this test, the connection withstands a bending moment emulating the real work conditions under gravity. Considering the behaviour hypothesis of continuous beam on multiple supports, the 3 points load test approaches the bending moment distribution over the connection, approximating the parabolic law by straight‐line segments. This test performed numerically is used to model the semi‐rigid behaviour of the sleeve connection, which significantly affects movements and the stresses developed by the multi‐span purlin, and therefore, influences its design (1), (2). The span length of the 3 points load test is related to the span length of the purlin whose connections are to be study. A change in the test span length involves a different multi‐span purlin. Previous work has dealt with the study of the sleeve connections for two profiles sections, small and large, varying the ratio lap length to depth, for the design of multi‐span purlins with span lengths of 6 and 11 m. This paper extends this study to consider larger span lengths. Thus, the range of the proposed formulations is expanded to include more slender purlins, expanding the knowledge for design optimization of these structural systems.